PENGARUH LAMA PERENDAMAN BENIH TEMBAKAU (NICOTIANA TABACCUM, LINN) TERHADAP VIABILITAS PERKECAMBAHAN - Syanzani, Syanzani; Tirtosastro, Samsuri; Agastya, I Made Indra (Fakultas Pertanian, 2018)
Problems encountered in the development of nature tobacco include the provision of quality seeds. The purpose of this study was to determine the effect of long-time immersion on potential viability (VP) of tobacco seeds and the effect of immersion duration on viability of sub optimum of tobacco seed. The experimental design used was Completely Randomized (RAL) with long immersion factors including 0 hours, 24 hours, 48 hours, 72 hours, and 120 hours. The results showed that the duration of immersion gave of significant influence on the power of sprouting, growing speed, uniformity of growth, length of stem and root length, seed not normal. Duration immersion of real effect on stem length, but did not give real effect to dry weight and wet weight. Permasalahan yang cukup rumit dihadapi pada pengembangan tembakau diantaranya adalah penyediaan benih bermutu yang cukup. Tujuan penelitian ini adalah untuk mengetahui pengaruh lama perendaman benih terhadap viabilitas potensial (VP) benih tembakau dan viabilitas sub optimum benih tembakau. Rancangan percobaan yang digunakan adalah Acak Lengkap (RAL) dengan faktor lama perendaman masing-masing 0 jam, 24 jam, 48 jam, 72 jam, dan 120 jam. Hasil penelitian menunjukkan bahwa lama perendaman memberikan pengaruh yang nyata pada daya berkecambah, kecepatan tumbuh, keseragaman tumbuh, panjang batang dan panjang akar. Lama perendaman pengaruh nyata terhadap panjang batang, namun tidak memberikan pengaruh nyata terhadap bobot kering dan bobot basah.